Evidence from ClinicalTrials.gov on the growth of Digital Health Technologies in neurology trials - Lars Masanneck; Pauline Gieseler; William J. Gordon; Sven G. Meuth; Ariel D. Stern (npj Digital Medicine, 2023)
Abstract Digital Health Technologies (DHTs) such as connected sensors offer particular promise for improving data collection and patient empowerment in neurology research and care. This study analyzed the recent evolution of the use of DHTs in trials registered on ClinicalTrials.gov for four chronic neurological disorders: epilepsy, multiple sclerosis, Alzheimer’s, and Parkinson’s disease. We document growth in the collection of both more established digital measures (e.g., motor function) and more novel digital measures (e.g., speech) over recent years, highlighting contexts of use and key trends.